XRF logging data from Nussloch loess cores - Rousseau, Denis-Didier; Antoine, Pierre; Pezard, Philippe Adrien; Henry, Gilles; Augustin, Laurent; De Moya, Alain; Moine, Olivier; Ardito, Luigi; Löscher, Manfred; Le Moal, Frédéric (PANGAEA, 2025)
The Nussloch Drilling Campaign (NUSS) involved drilling three loess sediment cores (85 mm in diameter) on April 21-25, 2019, on top of a loess hill at 49.31°N, 8.73°E, at an altitude of 215 m, close to the most recently described outcrop at the Nussloch reference site in Germany. Downhole logging was performed in the three drilling holes. Core S2, which has the most complete stratigraphy compared to previously published profiles, was analyzed using XRF core scanning. The name of the samples is given as NUSS for Nussloch, S2 for core S2, and C1-C11 for the subcore numbers. Depth is expressed in meters from the topsoil to the lowest level reached during drilling. The XRF data consists of the following elements: Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Cu, Zn, Ni, Br, Rb, Sr, Zr, and Pb, in counts. These raw data counts are followed by the following ratios: Ca/Sr, Rb/Sr, Rb/K, Fe/Al, Fe/Mn, Si/Al, Ti/Al, Ti/Zr, Zr/Rb, and Ca/Al. Measurements were conducted every 1 cm from the top of the sub-cores. The measurements were performed with a resolution of 5mm on the AVAATECH Core Scanner at the EDYTEM laboratory in Chambéry in June 2015. This investigation aimed to conduct a comprehensive coring to acquire a sedimentary archive to ensure the preservation of this distinctive Nussloch record for future research projects.
Keywords: last climatic cycle; loess paleosol sequence; XRF-core scanning